2017
DOI: 10.1111/jce.13151
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Left Atrial Bipolar Voltage and Scar Using Multielectrode Fast Automated Mapping versus Point‐by‐Point Contact Electroanatomic Mapping in Patients With Atrial Fibrillation Undergoing Repeat Ablation

Abstract: In AF patients undergoing repeat ablation, bipolar voltage is greater in certain LA segments with ME-FAM compared with PBP mapping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 17 publications
2
29
1
Order By: Relevance
“…We have found that typically there is a reduction in the chamber volume of some 10% after this respiratory gating filter is applied. Interestingly, this is very similar to the "overshoot" seen by Liang et al., who found LA area to be higher by ME‐FAM as compared to PbP mapping. In the absence of any other plausible explanation for differences in LA dimensions between PbP and MEM maps, this could be an important variable to consider.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…We have found that typically there is a reduction in the chamber volume of some 10% after this respiratory gating filter is applied. Interestingly, this is very similar to the "overshoot" seen by Liang et al., who found LA area to be higher by ME‐FAM as compared to PbP mapping. In the absence of any other plausible explanation for differences in LA dimensions between PbP and MEM maps, this could be an important variable to consider.…”
supporting
confidence: 87%
“…To the Editor We read with great interest the article by Liang et al 1 in the JCE. The authors are to be congratulated for their meticulous study comparing the left atrial voltage maps generated by point by point (PbP) and multi-electrode fast anatomical mapping (ME-FAM).…”
Section: Bipolar Voltage Analysis With Multi-electrode Mappingmentioning
confidence: 99%
“…Scar mapping was always performed in SR; if the patient was in AF cardioversion was carried out before mapping. The definition of scar included one of the following criteria: (a) absence of voltage or (b) low‐voltage abnormality with bipolar voltage amplitude, less than or equal to 0.2 mV was defined as a dense scar as reported previously …”
Section: Methodsmentioning
confidence: 99%
“…Tung et al demonstrated a linear relationship between bipolar voltages and increasing interelectrode spacing, which resulted in smaller low voltage area detected at a fixed threshold . Differences in scar area have been demonstrated in the left atrium when data were acquired with large‐tip single point catheter compared to multielectrode acquisition …”
Section: Chapter 4: Catheters For 3d Mapping—multi Vs Single Electrodmentioning
confidence: 99%